Phytotoxicity and leaf anatomy of young coffee plants subjected to herbicides exclusively and in associations - almeida, Rafael Jorge de; Henrique Gonçalves, Adenilson; Menicucci Netto, Pedro; Henrique Cruvinel Carneiro, Arthur; Toledo Castanheira, Dalyse; José Guimarães, Rubens; Rodrigues Carvalho, Gladyston (Coffee Science - ISSN 1984-3909, 2020)
The lack of human resources and the damage that weeds can cause to coffee plants are the causes of the growing demand for selective herbicides to be used in coffee farming. Thus, the objective of this study was to evaluate the phytotoxicity symptoms and leaf anatomical characteristics of young coffee plants submitted to application isolated herbicides and also in associations. An experiment was conducted in a protected environment in randomized blocks: four replications with coffee seedlings (Coffea arabica L.) cultivar “Topázio MG-1190”, grown in pots with a capacity of 11 liters of substrate. The herbicides applied, in isolation, were: pyrazosulfuron-ethyl (15 g ha-1), saflufenacil (49 g ha-1), imazetaphyr (100 g ha-1), iodosulfuron-methyl (3.5 g ha-1), chlorimuron-ethyl (15 g ha-1) and sethoxydim (184 g ha-1). The latter was used in associations with the others. In addition, a control without herbicides was used. Phytotoxicity symptoms were evaluated up to 49 days after application (DAA) and anatomical characteristics at 65 DAA. Saflufenacil alone and in association with sethoxydim caused visual phytotoxicity symptoms in the leaves and negatively influence in the characteristics of the epidermis thickness of the adaxial face (EAD), thickness of the palisade parenchyma (EPP), thickness of the spongy parenchyma (EPE) and thickness of the mesophyll (MES). The other herbicides, isolated or in associations, didn’t cause phytotoxicity symptoms, but had a negative influence in the anatomical parameters of the leaf blade, however they did not interfere with the paradermic parameters and the vascular bundle. Key words: Coffea arabica; leaf; selectivity; symptoms.